Tin Nanoparticles–Enhanced Optical Transportation in Branched CdS Nanowire Waveguides. Issue 17 (29th June 2018) - Guo, Shuai; Liu, Ruibin; Niu, Chunhui; Weller, Dieter; Hao, Yan; Zhang, Min; Li, An; Liang, Liang; Wang, Xiaoxia; Wang, Xiao; Yang, Bin; Li, Zi‐An; et al.
Abstract: High‐efficiency multichannel waveguiding components are desirable for integrated photonic systems to realize optical information processing and communication interconnection. Although different branched micro‐/nanostructures have been used as nanoscale multichannel waveguides, the propagation losses from their junctions are very high, which limits their applications in on‐chip photonic systems. Here, a new cadmium sulfide (CdS) nanowire branched heterostructure, with tin (Sn) nanoparticles implanted in its junctions, is achieved via a single‐step vapor deposition method. The self‐organized formation process of this structure is well investigated, through step‐by‐step observations during the growth. The implanted Sn nanoparticles in the junctions can act as strong light‐scattering centers, greatly improving the optical transportation from the backbone to the branches of the structure. Contrasting experiments demonstrate that the light‐guiding efficiency in the heterostructured nanowire branch waveguide is 20 times higher than that of the branched structures without Sn nanoparticles. Theoretical simulations further demonstrate the existence of Sn nanoparticles can greatly enhance the light scattering at the junctions and improve the light‐guiding performance. This kind of Sn‐CdS nanowire branched heterostructures may find promising applications for integrated photonic devices and systems. Abstract : High‐efficiency multichannel waveguides are achieved by implanting tin (Sn) nanoparticles in the junctions of cadmium sulfide (CdS) branched nanostructures via a single‐step vapor deposition method. The implanted Sn nanoparticles greatly improve the optical transportation as light‐scattering centers. Compared with the branched nanostructures without Sn nanoparticles, the guiding efficiency is improved by ≈20 times.